Is the light-emitting diode a better light source than fluorescent tube for phototherapy of neonatal jaundice in preterm infants? - Majid Mohammadizadeh; Fereshteh Kadkhodaei Eliadarani; Zohreh Badiei (Advanced Biomedical Research, 2012)
Background: Light-emitting diodes (LEDs) are light sources recently used for phototherapy in neonatal jaundice. We compared the efficacy and safety of LEDs with fluorescent phototherapy in the treatment of indirect hyperbilirubinemia. Materials and Methods: This controlled trial was conducted on preterm infants hospitalized in neonatal intensive care unit of Shahid Beheshti Hospital in Isfahan (Iran) who needed conventional phototherapy for uncomplicated indirect hyperbilirubinemia. Neonates received phototherapy through devices with LEDs or special blue fluorescent tubes. Primary outcomes included the rate of fall of total serum bilirubin (TSB, mg/dL/hour) and duration of phototherapy (hours). Secondary outcomes were treatment failure and side effects. Results: A total of 64 infants with gestational age of 33.5 ± 1.2 weeks, chronological age of 73.0 [SE = 7.3] hours, and weight of 1757.5 ± 147.6 gram were enrolled. The rates of fall of TSB were 0.20 [SE = 0.03] and 0.12 [SE = 0.01] mg/dL/hour in the LED and fluorescent groups, respectively (P = 0.472). Treatment duration was 37.5 ± 26.8 and 45.3 ± 32.1 hours in the LED and fluorescent groups, respectively (P = 0.292). There was no treatment failure in the two groups. Mild hyperthermia was occurred in 3.1% and 28.1% of infants in the LED and fluorescent groups, respectively (P = 0.006). Conclusions: LED light source is as effective as fluorescent tubes for phototherapy of preterm infants with indirect hyperbilirubinemia. Considering less frequent side effects, less energy consumption, longer life span, and lower costs, LED phototherapy seems to be a better option than current conventional phototherapy.